Memorandum of the Polish Episcopate to state authorities on matters of schools (1930-1936) - Jan Szczepaniak (Folia Historica Cracoviensia, 2000)
Contrary to popular belief, the relations between the Church and the state following the May coup (1926) were far from good. A particular bone of contention was the issue of teaching and religious education in schools. The article discusses the complex subject of mutual relations in the light of extant documents.